Computer-aided diagnosis system for thoracic computed tomography of rib fractures in older emergency patients: A preliminary study - Shan Xiong; Wenze Wu; Sibin Liu; Jianmin Cheng; Bing Wan (PLoS ONE, 2026)
The peculiarities of older individuals related to osteoporosis and hyperostosis may lead to a higher rate of misdiagnosis of rib fractures on computed tomography (CT) images in older than in middle-aged/young people when using radiologist-only reading. However, none of these studies on rib fracture computer-aided diagnostic (CAD) systems grouped patients by age or evaluated the value of using CAD in older patients. To address these gaps, we divided 1,012 blunt chest trauma emergency patients who underwent chest CT into middle-aged/young and older groups with a cutoff age of 60 years. CT images were read by six radiologists from three institutions (each with 7 years of experience in thoracic CT diagnosis) using two reading methods, radiologist-only and radiologist-CAD reading, to explore the value of a deep learning (DL)-based CAD system for detecting rib fractures in emergency older patients. The final findings of the independent panel consisting of two senior radiologists with or without a thoracic surgeon were set as the reference standard. The sensitivity was calculated by dividing the number of true positives by the overall number of fractures, as confirmed by an expert panel. The false positives per patient (FPPP) was calculated by dividing the number of false positives by the overall number of patients. Sensitivity and FPPP were used to evaluate the diagnostic efficiency. Sensitivity, FPPP, and reading time were compared between the two groups, as well as reading methods. The results showed the following: (1) Sensitivity for detecting fresh fractures using radiologist-only reading was lower in the older than in the middle-aged/young group (86.7% [95% confidence interval (CI): 86.3%, 91.7%] vs. 91.5% [95% CI: 89.9%, 92.9%], p < 0.05). With the assistance of the CAD system, the sensitivity increased in the older group to the same level as that in the middle-aged/young group using radiologist-only reading (92.5% [95% CI: 90.4%, 94.2%] vs. 91.5% [95% CI: 89.9%, 92.9%], p > 0.05). (2) The FPPP of fresh fractures with radiologist-only reading was higher in the older than in the middle-aged/young group (0.47 vs. 0.37, p < 0.05). With the assistance of the CAD system, the FPPP in the older group decreased to the same level as that in the middle-aged/young group when using radiologist-only or radiologist-CAD reading (0.37 vs. 0.37/0.39, p > 0.05). (3) The reading time of fresh fractures when using radiologist-only reading was longer in the older than in the middle-aged/young group (6.1 vs 5.4 min, p < 0.05). With the assistance of the CAD system, the reading time in the older group was reduced by approximately 36% ( p < 0.05). We conclude that the efficiency of intermediate-level radiologists in diagnosing fresh rib fractures by radiologist-only reading in older emergency patients was lower than that in middle-aged/young patients. When a DL-based CAD system assists radiologists, the diagnostic efficiency of identifying fresh fractures in older patients improves to the same level as independent radiologist-only reading in middle-aged/young patients while reducing the reading time.